2015
DOI: 10.1371/journal.pone.0132814
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Prevalence, Awareness, Treatment and Control of Hypertension during 2001-2010 in an Urban Elderly Population of China

Abstract: ObjectiveAs the most important risk factors of cardiovascular disease, pre-hypertension and hypertension are important public health challenges. Few studies have focused on the trends of pre-hypertension and hypertension specifically for the aging population in China. Given the anticipated growth of the elderly population in China, there is an urgent need to document the conditions of pre-hypertension and hypertension in this aging population.MethodsWe conducted two cross-sectional surveys of Chinese adults ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 40 publications
7
32
1
2
Order By: Relevance
“…Our study suggested that the dimension of Timeline Cyclical had a positive impact on PCS, which was inconsistent with Slotman's conclusions that a cyclical awareness was associated with lower physical functioning score . Elderly patients with hypertension frequently realised that they were old, which repeatedly stimulated their awareness of hypertension to adhere to healthy lifestyles and take antihypertensive drugs on time, hence improving their PCS. Simultaneously, this dimension showed a negative impact on MCS, as reported by Slotman et al …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study suggested that the dimension of Timeline Cyclical had a positive impact on PCS, which was inconsistent with Slotman's conclusions that a cyclical awareness was associated with lower physical functioning score . Elderly patients with hypertension frequently realised that they were old, which repeatedly stimulated their awareness of hypertension to adhere to healthy lifestyles and take antihypertensive drugs on time, hence improving their PCS. Simultaneously, this dimension showed a negative impact on MCS, as reported by Slotman et al …”
Section: Discussioncontrasting
confidence: 99%
“…Our study suggested that the dimension of Timeline Cyclical had a positive impact on PCS, which was inconsistent with Slotman's conclusions that a cyclical awareness was associated with lower physical functioning score. 17 Elderly patients with hypertension frequently realised that they were old, which repeatedly stimulated their awareness of hypertension to adhere to healthy lifestyles and take antihypertensive drugs on time, [43][44][45] hence improving their PCS. Simultaneously, this dimension showed a negative impact on MCS, as reported by Slotman et al 17,36 Consequence Positive and Negative This study indicated that the dimension of Consequences Positive was positively linked with both PCS and MCS, while the dimension of Consequences Negative was negatively linked with them, as reported by Slotman et al 36…”
Section: Timeline Cyclicalmentioning
confidence: 99%
“…The previously reported prevalence of hypertension, obesity, NAFLD, and diabetes in Chinese populations are 59.4% to 65.2%, 40,41 12.4%, 42 42%, 43 and 11.6%, 44 respectively. Thus, the hypertension and NAFLD results in our survey are consistent with previous reports, but the prevalence of obesity and diabetes in our survey is higher.…”
Section: Discussionmentioning
confidence: 85%
“…A Swedish study reported decreased mortality among people without disabilities and a decline in the prevalence of disability from 1991 to 2010 . In China, although hypertension seems to have increased among urban elderly populations, awareness, treatment and control have also increased .…”
Section: Epidemiology Of Agingmentioning
confidence: 99%